Civic Education in Secondary School in the Opinion of Students. Results of the Survey - Szparaga, Artur (Sensus Historiae, 2025)
The article presents the results of a survey conducted among hisgh school students on their opinions on school citizenship education and their interest in social and political issues. The respondents were also asked to assess the degree of transfer of knowledge in this field during HiT and WoS lessons. The involvement of young people in extracurricular social activities was also examined. The obtained results may become a voice in the discussion on the future shape of social education at school.